Group Exhibition- ArTwins Residency Program, Pafos European Cultural Capital. A Collaborative project with Elektro Moon Vision, Poland and Hungary. - Antoniou, Klitsa (My University, 2026)
ArTwins Residency Program, Pafos European Cultural Capital. A Collaborative project with Elektro Moon Vision, Poland and Hungary. . A Collaborative project with Elektro Moon Vision, Poland and Hungary.